Kecerdasan Buatan dan Keberlanjutan Sosial: Tinjauan Literatur tentang Dampak Teknologi Kemanusiaan dalam Pendidikan - Yulisia Rezky Kirana; Nurfadillah Salam; Riakurnaini; Hasrinah; Arifah Novia Arifin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of artificial intelligence (AI) has made a significant contribution to the transformation of global education, particularly in increasing the effectiveness, personalization, and efficiency of the learning process. However, behind this progress, new challenges have emerged related to the shift in human values, the loss of empathy, and the potential for dehumanization in education. This article aims to systematically review the relationship between AI, humanity, and social sustainability in education through the Systematic Literature Review (SLR) method with the PRISMA approach. Data were obtained from 480 Scopus-indexed publications (2020–2025) with the keywords "artificial intelligence AND education AND humanity." After a selection and filtering process, 17 relevant articles were obtained and analyzed using the VOSviewer tool to map the relationships between topics. The analysis results show that the topics of Artificial Intelligence and Education dominate research with high intensity, while the discussion of Humanity and Ethics is still rarely studied. Literature shows that AI has significant potential to support the achievement of the Sustainable Development Goals (SDGs), especially SDG 4 (quality education) and SDG 10 (reduced inequality), provided its implementation is grounded in ethics, empathy, and social justice. These findings emphasize that the direction of AI development in education must adopt a Human-Centered Artificial Intelligence (HAI) approach, which places humans at the center of technological control to realize sustainable, ethical, and socially just education.